The problem of the holistic development of a preschool child in the context of the modern concepts - Чаговець, А. І. (Scientific notes of the pedagogical department, 2018)
The key problems of the holistic development of a preschool child in the context of the modern concepts of childhood are stated and analyzed. The thoughts of the scientists who dealt with the solution of this problem are given. It is proved that it is in the childhood that the foundation of many phenomena and processes, that will occur in the future, is laid. That is why the investigation of the childhood as the social phenomena in the context of the modern concepts of childhood objectively causes changes in the theory of preschool pedagogy. It is indicated that scantily explored issue is the holistic development of a preschool child to his health and to himself. It is analyzed that in the modern domestic literature the scientific interest as to the study of social changes and new formations, which take place in a child’s cultural educational space in the era of the transformational changes in the society and the problems of adaptation to them, cannot be traced. It is proved that the development of a personality is the process of obtaining qualitative and quantitative changes in the own structure. Then, in the context of personal changes, the development of the individual is not the identity to the formation and forming. The consideration that was carried out became the basis for the theoretical analysis of the problem of the holistic development of a preschool child in the context of the modern concepts of childhood and gave an opportunity to determine that modern pedagogical concept of the holistic development of a child’s personality should be based on the theory of harmonious development of a personality. Thus, together they constitute the pedagogical concept of the holistic development and upbringing of a child as the subject of children’s activities. Accordingly, theoretical developments have made it possible to determine and realize new solution of educational problems,problems of teaching, life and activities of children, their attitude to the world and towards their own and, in general, the understanding of themselves in this world. The author’s position lies in the understanding that the concept of the holistic development and upbringing of a child should be realized in the model of personally complete education.